A Sancta Sapientia Medieval: enigma e mistério no teatro cristão de Rosvita de Ganderseheim - Martins, Gilberto Figueiredo [UNESP] (My University, 2011)
Within the scope of Literary Studies, theory, criticism, and historiography about the literature produced in the Middle Ages developed considerably from 1940 on, with the works of Ernst Curtius, Mikhail Bakhtin, and Erich Auerbach. In spite of the progress made, some specific aspects remain in the shadow, with incursions which were punctual though meaningful: that is the case of the critic fortunes about women‟s literary production in that period. Rosvita was a canoness and lived in the Benedictine convent of Gandersheim (Germany), in the 10th century A.D. Coming under Terence‟s influence, she wrote theater plays in Latin in which she figuratively presented theological issues in order to spread the Christian doctrine. The martyrdom issue deserved to be put in relief and was the focal point of the play Wisdom, which took place at the time of the Roman emperor Adrian. This paper analyzes that dramatic text discussing, at the end, how the categories of symbol, enigma, allegory, and mystery are organized by the author as expressive resources and structural elements.

No âmbito dos Estudos Literários, a teoria, a crítica e a historiografia acerca da literatura produzida na Idade Média avançaram muito, a partir de 1940, com as obras de Ernst Curtius, Mikhail Bakhtin e Erich Auerbach. A despeito dos progressos, permanecem na sombra alguns aspectos específicos, com incursões pontuais conquanto significativas: é o caso da fortuna crítica sobre a produção literária feminina no período. Rosvita foi canonisa e viveu no convento beneditino de Gandersheim (Alemanha), no século X d.C.. Influenciada por Terêncio, escreveu em latim peças teatrais nas quais apresentava figuradamente questões teológicas, a fim de difundir a doutrina cristã. O tema do martírio mereceu destaque, sendo o foco central da peça Sabedoria, ambientada no tempo do imperador romano Adriano. No ensaio, analisa-se este texto dramatúrgico, discutindo, ao final, de que modo as categorias de símbolo, enigma, alegoria e mistério são mobilizadas pela autora como recursos expressivos e elementos estruturais.
The Medieval Sancta Sapientia - enigma and mystery in Rosvita de Gandersheim s christian theater
Keywords: Christian medieval theater; Rosvita de Gandersheim; Martyrdom; Enigma and mystery; Teatro medieval cristão; Rosvita de Gandersheim; Martírio; Enigma e mistério